Peningkatan Komunikasi Matematis dan Hasil Belajar Siswa dengan Model Pembelajaran Resource Based Learning (RBL) - Bayu Agung Wicaksono; Satrio Wicaksono Sudarman; Nurul Farida (Limacon: Journal of Mathematics Education, 2019)
The purpose of this study is to determine the application of Resuorce-Based Learning (RBL) learning model in the Absolute Value material that can improve mathematical communication and students' learning outcomes. This research is Classroom Action Research (CAR) with planning, implementation, test cycles, and reflection. The subject in this research is a student in class X MA Hidayatul Ulum Seputih Raman. This data collection uses instruments in the form of a cycle test consisting of 5 questions for mathematical communication and a cycle test consisting of 5 questions for learning outcomes. Increased mathematical communication skills based on tests in the first cycle of 52.38% and increased in the second cycle to 71.43%. Then the increase in learning outcomes in the first cycle amounted to 42.86% and increased in the second cycle to 76.19%. Based on the results of the study it can be concluded that the application of the Resource-Based Learning (RBL) learning model can improve mathematical communication of class X MA Hidayatul Ulum Seputih Raman Academic Year 2019/2020.